KNOWLEDGE, ATTITUDE, PRACTICE OF TOXOCARIASIS AMONG PEOPLE IN NGHE AN PROVINCE, 2021 (Vietnam Journal of Community Medicine, 2021)
Objective: Description of knowledge, attitude, practice of Toxocariasis among people in Nghe An province, 2021.Method: A cross-sectional study was conducted on 400 people aged 18 and over.Results: The research results show that knowledge about Toxocariasis and the practice of preventing Toxocariasis of Nghe An people do not met the requirements. The average of knowledge score was only 23.6% of the expected point; over 80% of respondents had poor knowledge (81.8%). The proportion of people who do not keep dogs and cats and raise good dogs and cats accounts for only 37.8%; the percentage of people with bad living habits accounted for 88.0%. The attitude of the study subjects about Toxocariasis is quite good (62.7%). The average of attitude score was 71.4% of the expected point.Conclution: The knowledge and practice of research subjects about Toxocariasis is not good. The attitude of the research subjects about Toxocariasis is quite good. As such, there is a need for further analysis to find factors influencing people's knowledge and practices in the prevention of Toxocariasis.
Keywords: Knowledge, attitude, practice, Toxocariasis.